Faktor Yang Berhubungan Dengan Kecelakaan Kerja Terhadap Pekerja Mebel Sektor Informal Di Kecamatan Tembalang Kota Semarang Tahun 2021 - Ilham Maulana; Bayu Yoni Setyo Nugroho (Health Science Udinus, 2023)
Work accidents are unexpected and unexpected events that can cause casualties or loss of property. Furniture workers in the informal sector in Tembalang District, Semarang City still ignore the importance of using PPE, such as masks, gloves and other supporting PPE. Workers often experience incidents such as slipping, electrocution, cuts, falling objects, etc. The purpose of this study was to analyze the relationship between age, working period, role of co-workers, knowledge, use of PPE, and work accidents on informal sector furniture workers in Tembalang sub-district, Semarang City. Methods This research uses quantitative research with cross sectional method. Sampling in this study using Total Sampling or the population is the informal sector furniture workers with a total of 35 respondents. This data was collected using a questionnaire, and processed using Rank Spearman. Based on the results of the study, it showed that Age, Working Period, Role of Coworkers, Knowledge, and the use of PPE had no relationship with work accidents. P-value (age = 0.697), P-value (service period = 0.522), p-value (role of co-workers = 0.411), p-value (knowledge = 0.522). P-value (use of PPE = 0.505) for furniture workers in the informal sector, Tembalang district, Semarang city. The number of accidents is still categorized as high even though it was a minor accident. It is expected that business owners are able to provide supervision and provide information about work accidents and their prevention, provide PPE according to standards and complete. Meanwhile, workers are better off using PPE